Further evidence that concept mapping is not better than repeated retrieval as a tool for learning from texts. (December 2015) - Lechuga, M. Teresa; Ortega-Tudela, Juana M.; Gómez-Ariza, Carlos J.
Abstract: Karpicke and Blunt (2011) showed in college students that retrieval practice produced more learning from educational texts than concept mapping on a 1-week delayed test. This finding is surprising since concept mapping is thought to involve elaborative processing. Hence, the present study (N = 84; 76 females) aimed to examine whether the advantage of repeated retrieval remains when concept mapping is performed by ad hoc trained students or students who regularly utilise concept maps to prepare for exams. While the results essentially replicate Karpicke and Blunt's finding which shows that retrieval practice leads to better overall performance than concept mapping, this effect was less pronounced for people with experience using this technique than it was for trained participants. These findings point to the need to take retrieval-based learning into account in educational settings as well as to further investigate the conditions that may make retrieval activities more effective than concept mapping. Highlights: Repeated retrieval leads to better conceptual learning than concept mapping. A short training in concept mapping does not change this pattern. Even previous experience in concept mapping results in poorer performance than retrieval practice. Despite this, students do not see retrieval practice as a useful learning tool. Educators should be aware of the value attached to retrieval-based learning.